تطوير نظم المعلومات المحاسبية في القطاع العام الاقتصادي وفقاً لمتطلبات اقتصاد السوق الاجتماعي في سورية - زيـود, لطيـف; البهلول, محمـد; محمـد, نذيـر محمـد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن التطورات الاقتصادية والاجتماعية المتتالية التي حدثت في سورية, لاسيما في اعتماد منهج اقتصاد السوق الاجتماعي بدءاً من عام 2005, والتركيز على طاقة القطاعات الاقتصادية كافة (قطاع عام- قطاع خاص- وقطاع مشترك) على حد سواء والاستفادة من مقدراتها في خدمة عملية التنمية وعودة هدف الربح ومعايير الكفاءة والفعالية كعناوين أساسية لتقييم أداء المشروعات والوحدات الاقتصادية في مؤسسات وشركات القطاع العام الاقتصادي التي تعد المحاسبة المالية البيئة المناسبة لها, يجب تطوير نظم المعلومات المحاسبية في تلك المؤسسات والشركات بما ينسجم وتلك المتغيرات، ووفقاً لمتطلبات المعايير المهنية الحديثة لإنتاج المعلومات المحاسبية الملائمة. The successive economic and social developments in Syria, especially in adopting the concept of Social Market since 2005 and focusing on the abilities of all economic sectors (public sector, private sector and common sector), and benefiting of their abilities in serving the development and the return of the profit objective and the competence and effectiveness as main topics to evaluate the performance of the projects and the economic units in the institutions and companies of the economic public sector, which the financial accounting is the suitable environment for it, necessitate developing the Accounting Information Systems in these institutions and companies in accordance with these variables, and according to the needs of the modern professional standards to produce the suitable Accounting Information.